2021
DOI: 10.1038/s12276-021-00574-2
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy improves liver fibrosis via tumor necrosis factor superfamily 14 (LIGHT) through the JNK/TGF-β1 signaling pathway

Abstract: Splenectomy has been reported to improve liver fibrosis in patients with cirrhosis and hypersplenism. However, the mechanisms remain unclear. Tumor necrosis factor superfamily 14 (TNFSF14; also known as LIGHT) is highly expressed in the context of fibrosis and promotes disease progression in patients with fibrotic diseases such as pulmonary and skin fibrosis. Here, we determined whether splenectomy controls the production of LIGHT to improve liver fibrosis. Splenectomy reduced serum LIGHT levels in cirrhotic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The PI3K/AKT signaling pathway plays an important regulatory role in the progression of liver fibrosis [ 37 ]. In addition, activation of the ERK and JNK pathways is significantly positively correlated with activation of hepatic stellate cells, which exacerbates liver fibrosis [ [37] , [38] , [39] , [40] ]. AKAP12 knockout in hepatocytes activated PI3K-AKT pathway while had little or no effect on the JNK and ERK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway plays an important regulatory role in the progression of liver fibrosis [ 37 ]. In addition, activation of the ERK and JNK pathways is significantly positively correlated with activation of hepatic stellate cells, which exacerbates liver fibrosis [ [37] , [38] , [39] , [40] ]. AKAP12 knockout in hepatocytes activated PI3K-AKT pathway while had little or no effect on the JNK and ERK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…TNFSF14, which acts downstream of RelB, promotes hepatic stellate cell activation and exacerbates liver fibrosis ( 38 ). Staining with Masson 3 and Sirius Red confirmed that TP decreased collagen deposition around the portal fields in BDL mice ( Figures 5A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its presence in cholangiocytes, RelB is expressed in Kupffer cells ( 55 ) and hepatocytes ( 36 ). RelB-regulated TNFSF14 is presumed to promote hepatic stellate cell activation and the resulting liver fibrosis ( 38 ). Our assays of serum TNFSF14 levels indicated that TP reduced the BDL-induced increase in the TNFSF14 level; this may partly explain why TP relieves hepatic inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor superfamily 14 (TNFSF14) was the main driver of the former network with a markedly strong interaction between subclusters HEP2 and HEP5. This interaction could represent an underlying homeostatic mechanism between distinct hepatocytes responsible for regulating TGF- β 1 expression in liver fibrosis 60 . Interestingly, TGF β-centric communication was observed between MES8 and HEP7 cells (a COVID-19-specific subset), suggesting stressed hepatocytes could be driving fibrogenic HSC activation.…”
Section: Mainmentioning
confidence: 99%